2019
DOI: 10.1016/j.jid.2018.06.180
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte Cytokine Networks Associated with Human Melanocytic Nevus Development

Abstract: Melanocytes can group together in nevi, commonly thought to form because of intrinsic somatic mutations involving MAPK pathway activation. However, the role of the microenvironment, in particular keratinocytes, in nevogenesis is rarely studied. Melanocytes proliferate during the hair follicle growth phase and in some basal cell carcinomas, allowing us to construct keratinocyte gene expression clusters correlated with melanocyte activation. We asked whether such correlations are evident in the more subtle conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In fact, this is supported by a study showing that transgenic mice with a constitutive activated RET have a prolonged anagen phase of hair follicles along with accelerated melanin production in and around hair bulbs 14 . Upregulation of Shh and Edn1 in keratinocytes has been shown to cause hyperpigmentation and hypertrichosis 15 . Therefore, SHH and EDN1 could also play a role in the hypertrichosis reported herein.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In fact, this is supported by a study showing that transgenic mice with a constitutive activated RET have a prolonged anagen phase of hair follicles along with accelerated melanin production in and around hair bulbs 14 . Upregulation of Shh and Edn1 in keratinocytes has been shown to cause hyperpigmentation and hypertrichosis 15 . Therefore, SHH and EDN1 could also play a role in the hypertrichosis reported herein.…”
Section: Discussionsupporting
confidence: 72%
“…14 Upregulation of Shh and Edn1 in keratinocytes has been shown to cause hyperpigmentation and hypertrichosis. 15 Therefore, SHH and EDN1 could also play a role in the hypertrichosis reported herein. However, the rolling up of the scale edges of the hair cuticles, double mental foramina and abnormal condyles have not previously been reported.…”
Section: Discussionmentioning
confidence: 66%
“…Although in week 12 “N”, growth factors related to regeneration, for instance, JAG2, PDGFC, PDGFB, and FBRS, have higher expression rates than in “A”, some suppressive factors like OSM or other more potent factors repress the regeneration events in “N”. In addition, in week 12, the expression level of KITLG – a stem cell factor [53] in “N” is similar to “A”, indicating that the regeneration event is terminated for a while. This could explain why the regeneration activity in week 12 “N” is suppressed.…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported single nucleotide polymorphisms (SNPs) on chromosomes 6 (mapping in the IRF4 gene), 9 (in the MTAP and DOCK8 genes and in the 9q31.2 region), 12 (in the KITLG gene), and 22 (in the PLA2G6 gene) as the most highly predictive of the number of nevi. IRF4 is a transcription factor implicated in melanocyte pigmentation and proliferation [ 25 ]; MTAP acts in polyamine metabolism [ 26 ]; DOCK8 regulates signal transduction [ 27 ]; KIT -ligand ( KITLG ) acts in different biological pathways, including melanocyte development and melanin synthesis [ 28 ]; and PLA2G6 has a crucial role in the regulation of membrane dynamics and homeostasis [ 29 ]. Thus, multiple pathways appear to be involved in the susceptibility to nevi, supporting a polygenic model of nevogenesis lacking high-penetrance nevus genes.…”
Section: Nevimentioning
confidence: 99%